CREATIVE INDUSTRIES AND MSME STRATEGIES THROUGH OPTIMIZING HUMAN RESOURCES IN UTILIZING DEMOGRAPHIC BONUSES BY USING THE TQM METHOD - Shinta Ratnawati; Hanung Eka Atmaja (Jurnal Ilmu Sosial dan Humaniora, 2021)
Indonesia is predicted to get a demographic bonus in 2020-2030. A demographic bonus will be beneficial if Indonesia's human development index (HDI) is high quality. In ASEAN, HDI Indonesia ranks 6th out of 10 countries. The government is intensively pushing the creative industries and MSMEs to become agents of development to maximize the demographic bonus that Indonesia will face. The government is targeting at least 2020 to print 1,000 digital technopreneurs, one million farmers and fishers, and eight million SMEs going digital. The purpose of this study is to determine the general picture, the benefits, and the extent to which HR influences the creative industry and MSMEs. Total Quality Management is an approach that tries to maximize the competitiveness of organizations through several improvements: increasing human resources, the quality of products, services, processes, and the environment. The results of research with the application and implementation of the concept of Total Quality Management (TQM) in the creative industry and MSMEs that human resources have a significant role in increasing creativity to produce products according to market demand, optimizing the use of information and communication technology, and increasing creative industries with fellow creative industries as well as colleges.